Family-based enterprises in north-Sharqiyah region of Oman: opportunities and challenges. (2017) - Chaudhry, Iffat S.; Harthy, Said Al; Shibli, Said Al; Sultan, Nabil; Maurice, Jean G.
Family-based micro-, small- and medium-sized businesses are of an absolute importance for the social and economic development of the Sultanate of Oman which is in dire need of diversifying its economy from the fossil-based energy sector and combating increases in youth unemployment. The current investigation has been undertaken to assess the current situation of family-based firms in north A'Sharqiyah region of Oman. The study determines the opportunities available to the entrepreneurs, along with the challenges faced by them in developing their business. Interviews were conducted of the owners/directors of 37 family-based businesses working in north A'Sharqiyah region. The findings highlighted the major obstacles faced by the entrepreneurs in managing their business affairs. The findings have implications for regulatory bodies.